Identification and selection of normalization controls for quantitative transcript analysis in Blumeria graminis. (9th October 2015) - Pennington, Helen G.; Li, Linhan; Spanu, Pietro D.
Summary: The investigation of obligate biotrophic pathogens, for example B lumeria graminis, presents a number of challenges. The sensitivity of many assays is reduced because of the presence of host material. Furthermore, the fungal structures inside and outside of the plant possess very different characteristics. Normalization genes are used in quantitative real‐time polymerase chain reaction (qPCR) to compensate for changes as a result of the quantity and quality of template material. Such genes are used as references against which genes of interest are compared, enabling true quantification. Here, we identified six potential B . graminis and five barley genes for qPCR normalization. The relative changes in abundance of the transcripts were assayed across an infection time course in barley epidermis, in B . graminis epiphytic structures and haustoria. The B . graminis glyceraldehyde‐3‐phosphate dehydrogenase (GAPDH), actin (ACT) and histone 3 (H3) genes and the barley GAPDH, ubiquitin (UBI) and α‐tubulin 2B (TUBA2B) genes were optimal normalization controls for qPCR during the infection cycle. These genes were then used for normalization in the quantification of the members of a Candidate Secreted Effector Protein (CSEP) family 21, a conidia‐specific gene and barley genes encoding putative interactors of CSEP0064. The analysis demonstrates the importance of identifying which reference genes are appropriate for each investigation.